The Islamic views on counterproductive work behaviour: Islamic work ethics perspectives - Mohd Firdaus Kozako, Intan Nurul ‘Ain; Annual, Norazlan; Abdul Karim, Zatul Himmah; Shamsuddin, Noorazzila; Mustafa @ Busu, Zanirah (Universiti Teknologi MARA, Kelantan, 2018)
This paper aims to look at a religious view on counterproductive work behaviour (CwB) that is currently happening in organizations. This concept paper will discuss the issues involving counterproductive work behaviour in the perspectives of Islam by comparing with the Islamic Work Ethic (IWE). Obviously, no religions agree that counterproductive work behaviour is an ethical conduct. Nevertheless, counterproductive work behaviour was so common even to those who are working at Islamic organizations.